Comparative Proteomic Analysis Provides New Insights into the Development of Haustorium in Taxillus chinensis (DC.) Danser. (28th July 2022) - Pan, Limei; Wan, Lingyun; Song, Lisha; He, Lili; Jiang, Ni; Long, Hairong; Huo, Juan; Ji, Xiaowen; Hu, Fengyun; Fu, Jine; Wei, Shugen
Abstract : Taxillus chinensis is an important medicinal and parasitic plant that attacks other plants for living. The development of haustorium is a critical process, imperative for successful parasitic invasion. To reveal the mechanisms underlying haustorium development, we performed an iTRAQ-based proteomics analysis which led to the identification of several differentially abundant proteins (DAPs) in fresh seeds (CK), baby (FB), and adult haustoria (FD). A total of 563 and 785 DAPs were identified and quantified in the early and later developmental stages, respectively. Pathway enrichment analysis revealed that the DAPs are mainly associated with metabolic pathways, ribosome, phenylpropanoid biosynthesis, and photosynthesis. In addition, DAPs associated with the phytohormone signaling pathway changed markedly. Furthermore, we evaluated the content of various phytohormones during different stages of haustoria development. These results indicated that phytohormones are very important for haustorium development. qRT-PCR results validated that the mRNA expression levels were consistent with the expression of proteins, suggesting that our results are reliable. This is the first report on haustoria proteomes in the parasitic plant, Taxillus chinensis, to the best of our knowledge. Our findings will enhance our understanding of the molecular mechanism of haustoria development.